A novel method for the isolation of subpopulations of rat adipose stem cells with different proliferation and osteogenic differentiation potentials - Rada, Tommaso (2011)
Bone marrow has been the elected cell source of studies published so far concerning bone and cartilage tissue-engineering approaches. Recent studies indicate that adipose tissue presents significant advantages over bone marrow as a cell source for tissue engineering. Most of these studies report the use of adipose stem cells (ASCs) isolated by a method based on the enzymatic digestion of the adipose tissue and on the ability of stem cells to adhere to a cell culture plastic surface. Using this method, a heterogeneous population was obtained containing different cell types that have been shown to compromise the proliferation and differentiation potential of the stem cells. This paper reports the development and optimization of a new isolation method that enables purified cell populations to be obtained that exhibit higher osteogenic differentiation and/or proliferation potential. This method is based on the use of immunomagnetic beads coated with specific antibodies and it is compared with other methods described in the literature for the selection of stem cell populations, e.g. methods based on a gradient solution and enzymatic digestion. The results showed that the isolation method based on immunomagnetic beads allows distinct subpopulations of rat ASCs to be isolated, showing different stem cells marker expressions and different osteogenic differentiation potentials. Therefore, this method can be used to study niches in ASC populations and/or also allow adipose tissue to be used as a stem cell source in a more efficient manner, increasing the potential of this cell source in future clinical applications.